Biomedical Technology – 2011 and Beyond - Vladimir Blazek (Communications - Scientific letters of the University of Zilina, 2011)
Fundamental advances in knowledge and understanding across a range of specialized fields in medicine, biology, engineering and other natural sciences; the discovery of novel sensor concepts for non-invasive function diagnostics of diseases and abnormal developments at early stages; the development of cost-effective, automated measuring procedures that can be miniaturized to the cellular and molecular level; the implementation of new imaging techniques for optimized therapies and therapy-control – these are just some of the reasons for the rapid growth of biomedical technology as an independent field of study and research in the past decades.Furthermore, in a contemporary health-policy context marked by health-insurances’, patients’ and society’s demands for reduced health spending, the advances and high-quality, interdisciplinary knowledge available in biomedical technology today have a highly significant role to play in medico-technical process optimization and cost-benefit analyses.There is increasing demand for highly competent staff with the interdisciplinary qualifications and open-mindedness needed to venture beyond the core areas – staff capable of realizing innovative, individual advances in a structured way, while also advancing the field as a whole. Thus the question as to the future prospects of biomedical technology and the young generation of students, researchers and professionals can be decisively answered: “exciting, promising and highly rewarding.”All in all, biomedical technology continues to be both an excellent profession and field of study and research at the intersection of animate and inanimate matter – though excellence always comes with responsibility.